Prepartum fatty acid supplementation in sheep. IV. Effect of calcium salts with eicosapentaenoic acid and docosahexaenoic acid in the maternal and finishing diet on lamb liver and adipose tissue during the lamb finishing period1. (7th May 2019) - Coleman, Danielle N; Carranza Martin, Ana C; Jin, Yukun; Lee, Kichoon; Relling, Alejandro E
Abstract: The objective of this study was to evaluate the effects of eicosapentaenoic acid (EPA ) and docosahexaenoic acid (DHA ) supplementation to ewes during late gestation on finishing lamb liver and adipose tissue fatty acid (FA ) profile and gene expression. Lambs born from ewes supplemented with Ca salts of EPA + DHA, or palm FA distillate (PFAD ) high in palmitic and oleic acid at 0.39% DM during the last 50 d of gestation were used. Lambs were weaned at 61 d of age and adapted to a high concentrate diet for 1.5 mo. After adaptation, 74 lambs (28 pens) were blocked by sex and BW and used in a 2 × 2 factorial arrangement of treatments using the factors of dam supplementation (DS ) and lamb supplementation (LS ) of Ca salts of EPA + DHA or PFAD at 1.48% DM. Lambs were slaughtered after 42 d and liver and adipose tissue collected for FA and gene expression analysis. Liver concentrations of EPA and DHA were greater ( P < 0.01) with LS of EPA + DHA vs. PFAD during the finishing period. In adipose tissue, a lamb × dam interaction was observed for EPA ( P = 0.02) and DHA ( P = 0.04); LS of EPA + DHA increased EPA and DHA, but the increase was greatest in lambs born from ewes supplemented with PFAD. No lamb × dam treatment interactions were observed for gene expression in liver tissue ( P > 0.10). Hepatic mRNA abundance of hormone-sensitive lipase ( HSL ; P = 0.01) was greater in lambs born from EPA + DHA ewes vs. lambs from PFAD ewes. mRNA expression of stearoyl-CoA desaturase ( P < 0.01), fatty acid synthase ( P = 0.01), Δ 5 -desaturase ( P < 0.01), and Δ 6 -desaturase ( P < 0.01) were decreased in liver of EPA + DHA lambs. A significant lamb × dam diet interaction was observed for elongation of very long chain fatty acid 2 in adipose tissue ( P = 0.01); lambs supplemented with the same FA as their dams had lower expression. Expression of HSL tended ( P = 0.08) to be decreased in adipose of EPA + DHA lambs born from EPA + DHA ewes. The changes in mRNA expression suggest that lipogenesis decreased, and lipolysis increased in lamb liver with EPA + DHA vs. PFAD supplementation during the finishing period. In adipose tissue, changes suggest that lipogenesis decreased in lambs born from EPA + DHA supplemented dams and supplemented with EPA + DHA during the finishing period. In addition, these results suggest an interaction between supplementation of FA to dams during late gestation on lamb response of adipose tissue, but not liver, to FA supplementation during the finishing period.